2021
DOI: 10.1016/j.jamda.2020.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Sarcopenia in Singaporean Adults—The Yishun Study

Abstract: Objectives: To describe the normative values of sarcopenia among community-dwelling adults (21 years of age); compare the prevalence of sarcopenia using Asian Working Group for Sarcopenia criteria, 2014 (AWGS2014), Asian Working Group for Sarcopenia criteria, 2019 (AWGS2019), and European Working Group on Sarcopenia in Older People criteria, 2018 (EWGSOP2) guidelines; and identify factors associated with sarcopenia. Design: Participants were recruited through random sampling. Sarcopenia assessments were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
71
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 40 publications
17
71
1
3
Order By: Relevance
“…The present study is among the few attempts to investigate the prevalence of probable sarcopenia according to the AWGS 2019 criteria. The prevalence of probable sarcopenia in the current study is consistent with that reported in a study conducted in Thailand (28.2%, N = 330) and Japan (30.3%, N = 552), but much higher than that reported in a study from Singapore (14.0%, N = 542) and in the UK Biobank study (5.3%, N = 499,046) 12 , 15 , 26 , 28 . Our findings suggest the usefulness of dynamometers for the easy detection of probable sarcopenia.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The present study is among the few attempts to investigate the prevalence of probable sarcopenia according to the AWGS 2019 criteria. The prevalence of probable sarcopenia in the current study is consistent with that reported in a study conducted in Thailand (28.2%, N = 330) and Japan (30.3%, N = 552), but much higher than that reported in a study from Singapore (14.0%, N = 542) and in the UK Biobank study (5.3%, N = 499,046) 12 , 15 , 26 , 28 . Our findings suggest the usefulness of dynamometers for the easy detection of probable sarcopenia.…”
Section: Discussionsupporting
confidence: 91%
“…We reported that over 50% of our cohort of community-dwelling older adults living alone was at risk of sarcopenia. This proportion is much higher than that reported in a cohort study conducted in Hong Kong using the SARC-F (3.8%) and the AWGS 2014 criteria (7.3%), a survey conducted in China using the AWGS 2014 criteria (6.4–19.3%), a study conducted in Singapore using dual-energy X-ray absorptiometry according to the AWGS 2019 criteria (13.6%), and a large prospective epidemiological study (United Kingdom Biobank) using a bioimpedance analysis according to the EWGSOP2 criteria (6.4%) 9 , 11 , 12 , 26 , 27 . This difference in sarcopenia prevalence could be partially attributed to the different diagnostic tools used in the studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of sarcopenia depends on the setting and the definition used. According to the Asian Working Group for Sarcopenia (AWGS) 2019 criteria, the prevalence of sarcopenia is approximately 14.9-32.2% in community-dwelling populations and 45.5-61.1% in clinic or hospital populations [4][5][6][7]. With aging populations, sarcopenia is likely to become a much more widespread public health concern worldwide in the future.…”
Section: Introductionmentioning
confidence: 99%